Potential for soil organic carbon sequestration in grasslands in East African countries: A review - Tessema, Bezaye; Sommer, Rolf; Piikki, Kristin; Söderström, Mats; Namirembe, Sara; Notenbaert, An Maria Omer; Tamene, Lulseged D.; Nyawira, Sylvia; Paul, Birthe K. (Wiley, 2020)
Grasslands occupy almost half of the world's land area. Soil organic carbon (SOC) is a key indicator of soil fertility and grassland productivity. Increasing SOC stocks (so‐called SOC sequestration) improves soil fertility and contributes to climate change mitigation by binding atmospheric carbon dioxide (CO2). Grasslands constitute about 70% of all agricultural land, but their potential for SOC sequestration is largely unknown. This review paper quantitatively summarizes observation‐based studies on the SOC sequestration potential of grasslands in six East African countries (Burundi, Ethiopia, Kenya, Rwanda, Tanzania and Uganda) and seeks to identify knowledge gaps related to SOC sequestration potential in the region. In the studies reviewed, SOC stocks in grasslands range from 3 to 93 Mg C/ha in the upper 0.3 m of the soil profile, while SOC sequestration rate ranges from 0.1 to 3.1 Mg C ha‐1 year‐1 under different management strategies. Grazing management is reported to have a considerable impact on SOC sequestration rates, and grassland regeneration and protection are recommended as options to stimulate SOC sequestration. However, a very limited number of relevant studies are available (n = 23) and there is a need for fundamental information on SOC sequestration potential in the region. The effectiveness of potential incentive mechanisms, such as payments for environmental services, to foster uptake of SOC‐enhancing practices should also be assessed.